Proceeding of the International Technical Meeting of the Satellite Division of the Institute of Navigation / [cakera padat] - 475045 International Technical Meeting of the Satellite Division of the Institute of Navigation; Institute of Navigation (Washington, D. C. : Institute of Navigation, 1997)
System requirements: Windows or MacOS with Acrobat Reader